Can different occlusal positions instantaneously impact spine and body posture? : A pilot study using rasterstereography for a three-dimensional evaluation - März, Karoline; Adler, Werner; Matta, Ragai-Edward; Wolf, Linda; Wichmann, Manfred; Bergauer, Bastian (Journal of Orofacial Orthopedics / Fortschritte der Kieferorthopädie, 2017)
Orthodontists influence dental occlusion directly. To suggest any link between dental occlusion and body posture is highly contentious, as evidenced by the literature. Rasterstereography, an optical technique that enables three-dimensional (3D) body measurements to be collected, has not yet been used to impartially examine whether different occlusal positions could instantaneously alter spine and body posture. We therefore set out to use this technique to nonsubjectively evaluate this question under static conditions.Optical body scans were collected for 44 subjects, using the Diers formetric 4D system, for seven different mandible positions. In total, ten spinal and body posture parameters were assessed (trunk inclination, trunk imbalance, pelvic tilt, pelvic torsion, fleche cervicale, fleche lombaire, kyphotic angle, lordotic angle, surface rotation, and lateral deviation) for each mandible position and compared with scans performed with habitual intercuspation (HIC).Significant body posture deviations were found for the fleche cervicale (position of the mandible: right eccentrically), fleche lombaire (positions of the mandible: physiologic rest position, cotton rolls on both sides, bite elevation 1 mm), and the kyphotic angle (positions of the mandible: cotton rolls on both sides, right eccentrically). No other significant differences were detected.Data for the parameters that varied with different dental occlusions generated high standard deviations. Therefore, within the limitations of this pilot study, we could not conclusively associate dental occlusion to an instantaneous impact on the tested parameters. The posture changes that we detected could also have arisen from individual neuromuscular compensation; a possibility that must now be ruled-in, or out, by further research studies with a higher number of subjects.
EVALuna2:24443

Three-dimensional evaluation of mandibular deformation during mouth opening - Wolf, Linda; Bergauer, Bastian; Adler, Werner; Wichmann, Manfred; Matta, R. E. (International Journal of Computerized Dentistry, 2019)
Aim: Deformation of the mandible presents a major challenge for many dentists, both in conventional prosthetic supraconstructions and in complex implant restorations. This study aimed to evaluate the three-dimensional (3D) deformation of the mandible in vivo with scannable impression material and an industrial optical scanner.
CRIS-Team WoS Importer:2019-03-29

Three-dimensional evaluation of mandibular deformation during mouth opening - Wolf, Linda; Bergauer, Bastian; Adler, Werner; Wichmann, Manfred; Matta, Ragai Edward (International Journal of Computerized Dentistry, 2019)
Aim: Deformation of the mandible presents a major challenge for many dentists, both in conventional prosthetic supraconstructions and in complex implant restorations. This study aimed to evaluate the three-dimensional (3D) deformation of the mandible in vivo with scannable impression material and an industrial optical scanner. Materials and methods: In the present study, 20 female and 20 male subjects were examined. In each case, two impressions were made with polyvinylsiloxane: one with the mouth slightly open, and a second with the mouth wide open. The impressions were digitized with an industrial optical scanner and transformed into a virtual model. The two corresponding models were digitally superimposed over all the teeth. Then, an individual local coordinate system was assigned to each individual tooth. Subsequently, a best-fit procedure was performed for each individual tooth. Finally, the open- and closed-mouth models were compared by calculating the differences and rotations in the individual axes. This procedure was performed individually for each tooth. Results: The mean deviations in the x-, y-, and z-coordinates ranged from 0.011 mm at the canines to 0.232 mm at the molars. Larger discrepancies were observed in the female subjects than in the male subjects; however, these differences were not statistically significant. Conclusion: The results demonstrated that the posterior region of the mandible deformed when the mouth was maintained in a wide-open position. Therefore, this position should be avoided when performing dental impressions. Moreover, potential negative consequences of this mandibular deformation should be taken into consideration when planning wide-span fixed dental restorations.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Abdruck; Biegung; Deformation; Deformation; Dreidimensional; Flexure; Impression; Mandible; Prosthetic; Prothetisch; Threedimensional (3D); Unterkiefer